Motion analysis of the hydraulic ladder - Frankovský, Peter; Delyová, Ingrid; Trebuňová, Marianna; Čarák, Peter; Kicko, M.; Kurylo, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
This paper is aimed at a dynamic analysis of a hydraulically lifted ladder by means of analytical and numerical calculations. The solutions used in the dynamic analysis of mechanical systems were used in the analytical solution. A numerical model was created to verify the achieved results of the solved mechanical system with simulation of its motion.
Keywords: motion; hydraulic lifting ladder; velocity; acceleration